A preliminary study on the reference intervals of vitamin K in some areas of Beijing with normal physical examination population - Lin Chen; Meiqi Chen; Shi Cheng; Jiaxin Fei; Dan Xu; Xueyun Hou; Nannan Li; Yuliang Yuan; Guijian Liu; Cheng An (Journal of Nutritional Science)
The vitamin K (VK) levels vary greatly among different populations and in different regions. Currently, there is a lack of reference intervals for VK levels in healthy individuals, The aim of this study is to establish and validate the reference intervals of serum vitamin K1 (VK1) and vitamin K2 (VK2, specifically including menaquinone-4 (MK4) and menaquinone-7 (MK7)) levels in some healthy populations in Beijing. Serum VK1, MK4, and MK7 were firstly measured by high-performance liquid chromatography and mass spectrometry in 434 subjects. The reference intervals for three indicators were established by calculating the data of 2.5 and 97.5 percentiles. Finally, preliminary clinical validation was conducted on 60 apparent healthy individuals undergoing physical examination. In the young, middle-aged, and elderly groups, the reference intervals of VK1 were 0.180 ng/mL ∼ 1.494 ng/mL, 0.247 ng/mL ∼ 1.446 ng/mL, and 0.167 ng/mL ∼ 1.445 ng/mL, respectively. The reference intervals of MK4 were 0.009 ng/mL ∼ 0.115 ng/mL, 0.002 ng/mL ∼ 0.103 ng/mL, and 0.003 ng/mL ∼ 0.106 ng/mL, respectively. The reference intervals of MK7 were 0.169 ng/mL ∼ 0.881 ng/mL, 0.238 ng/mL ∼ 0.936 ng/mL, and 0.213 ng/mL ∼ 1.012 ng/mL, respectively. The reference intervals had been validated by the samples of healthy individuals for physical examination. In conclusion, the reference intervals of VK established in this study with different age groups have certain clinical applicability, providing data support for further multicentre studies.